Projected depletion of high mountain Asia glaciers by 2100: linking mass loss to asynchronous peak runoff - Muhammad Mannan Afzal; Fuming Xie; Yu Zhu; Adeel Ahmad Nadeem; Fazli Hameed; Yi Luo; Tandong Yao; Fubao Sun; Xin Wang; Qiao Liu; Jyoti Karki; Jun Zhou; et al. (Journal of Hydrology, 2026)

Interfacial construction of Co-MOF/NiCu-MOF for enhanced visible-light-driven peroxymonosulfate activation and ciprofloxacin degradation: Mechanistic insights, kinetics and stability study - Raza Ullah; Nasim Ullah; Abdul Qadir; Muzamil Ahmad; Alamgir; Muhammad Fayaz; Muhammad Rafiq; Adeel Ahmed; Muhammad Adnan; Fangqing Wang; Bing Yu; Hailin Cong (Journal of Environmental Chemical Engineering, 2026)

Rationalizing bud load for grapevine cv sugraone for balanced yield and superior fruit quality in a warm semi-arid region - Muhammad Hashir Khan; Irfan Ali; Muhammad Tahir Akram; Mahmood-ul-Hassan; Adeel Anwar; Rizwan Rafique (Acta Physiologiae Plantarum, 2026)

Effectiveness of machine learning and deep learning techniques for multi-horizon weather forecasting - Abdullah Sami; Muhammad Bilal; Usman Habib; Adeel Ashraf Cheema (Meteorology and Atmospheric Physics, 2026)

Heterogeneous impacts of climate, technology, and energy shocks on agricultural productivity in the United States: evidence from wavelet QQ regression - Mumtaz Ali; Muhammad Adeel (Euro-Mediterranean Journal for Environmental Integration, 2026)

WheatSim: A process-based wheat model linking organ development, plant architecture, and field-scale responses under environmental variability - Zhuangji Wang; Dennis Timlin; Xiaocui Wu; Elnaz Ebrahimi; Bin Peng; Kirsten Paff; Christine Chang; Eunjin Han; Lisa Fultz; Amir Sadeghpour; Ezekiel Ahn; David Fleisher; et al. (Computers and Electronics in Agriculture, 2026)

Material flow analysis of polyurethane foams in the EMEA region: Mapping waste streams and circular economy opportunities - Matthew Porters; Cristina Moyaert; Muhammad Adeel; Christophe de Graaf; Zoë De Herdt; Denis Hicks; Christophe M.L.Vande Velde; Philippe Nimmegeers; Pieter Billen (Resources, Conservation and Recycling, 2026)

Coupled metabolomics and digital pathology to elucidate mechanistic pathways in earthworm (Eisenia fetida) exposed to environmentally relevant lithium - Noman Shakoor; Muhammad Adeel; Imran Azeem; Samama Tariq; Melanie Kah; Buana Suefo; Yukui Rui (Applied Soil Ecology, 2026)

Retraction notice to “TiO2/SiO2 decorated carbon nanostructured materials as a multifunctional platform for emerging pollutants removal” [Sci. Total Environ. 688 (2019) 299–311] - Tahir Rasheed; Muhammad Adeel; Faran Nabeel; Muhammad Bilal; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Textile & clothing industry, economic growth, and energy use: navigating the carbon emissions challenge in Türkiye - Hüseyin Çelik; Mumtaz Ali; Muhammad Adeel (Euro-Mediterranean Journal for Environmental Integration, 2026)

Evaluation of Larvicidal Potential of Nepeta cataria and Cymbopogon nardus Essential Oils Against Aedes aegypti - Iqra Shafeeq; Sammina Mahmood; Adeel Sattar; Qamar Niaz; Mian Abdul Hafeez; Muhammad Ilyas; Muhammad Shahid Mahmood (Acta Parasitologica, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Multimodal bioactivities and COX-2 targeted anti-inflammatory mechanism of enzyme-assisted ultrasonic extracted capsicum and zingiber oleoresins: An integrated computational and experimental study - Muhammad Adeel Razzaq; Muhammad Shahid; Zahid Mushtaq; Bushra Akhtar (Food Bioscience, 2026)

Investigating thermal performance of PCM-integrated solar windows with multi-discharging modes in a humid subtropical climate - Muzaffar Ali; Ubaid ur Rehman; Nadeem Ahmed Shiekh; Hafiz Muhammad Adeel Hassan; Muhammad Usman; Andrea Ferrantelli; Müslüm Arıcı (Energy and Buildings, 2026)

Disaster management technology and approaches: a focus on heterogeneous systems - Muhammad Haris; Sajjad Keshtkar; Adeel Anjum; Madiha Haider Syed; Hirohisa Kojima; Rafiq Ahmad (Environment Systems and Decisions, 2026)

Novel Silver Nickel Ferrite Nanocomposite: Synthesis, Characterization, Comparative Remediation of Eriochrome Black T - Maria Khan; Sultan Muhammad; Ammara Aftab; Zooraisha Adeel; Muhammad Waseem (Water, Air, & Soil Pollution, 2026)

Retraction Note: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2026)

The SPAR facility: insights on a legacy with continued relevance for agriculture - Muhammad Adeel Hassan; Sahila Beegum; Christine Yao-Yun Chang; Dennis Timlin; David Fleisher; Chittaranjan Ray; Vangimalla Reddy; Kambham Raja Reddy (Computers and Electronics in Agriculture, 2026)

Navigating mobility in later life: How vehicle access and community context shape travel behaviour among older adults - Muhammad Adeel; Asad J. Khattak; Moetasim Ashfaq (Travel Behaviour and Society, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Advancing nano-enabled Agriculture from Precision Application To Environmental Risk and Sustainability Assessment - Jiahui Feng; Muhammad Adeel; Yukui Rui (Current Pollution Reports, 2026)

Recovery of multiple polyol grades from complex flexible polyurethane foams by depolymerization with alkanolamines - Zoë De Herdt; Muhammad Adeel; Lukasz Pazdur; Matthew Porters; Victor Beeckmans; Jonas Cassimon; Christophe M.L. Vande Velde; Pieter Billen (Waste Management, 2026)

Remote sensing and multi-method statistical analysis of snow cover variability and hydrological responses in the Upper Indus Basin - Nasir Abbas; Shah Fahd; Ninglian Wang; Muhammad Zubair; Adeel Ahmad Nadeem; Zeeshan Zafar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Nigella sativa L. (Black cumin) seeds impart protective effects against Staphylococcus aureus induced septic arthritis through the modulation of immune and inflammatory responses - Muhammad Aamir Shaheen; Adeel Sattar; Huma Rao; Amjad Riaz; Abdul Basit (Food Bioscience, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Management of canola aphids (Hemiptera: Aphididae) using potassium silicate (K2SiO3) in integration with Chrysoperla carnea Stephens - Dilawar Abbas; Umer Liaqat; Habib Ali; Tehniyat Fatima; Ammara Riaz; Inzamam Ul Haq; Zahid Mahmood Sarwar; Muhammad Abaid Ullah; Muhammad Adeel Ghafar; Kamran Haider; Muhammad Lubaid Khalid; Modhi O. Alotaibi; et al. (Journal of Plant Diseases and Protection, 2026)

First Report of Aspergillus aculeatus Colonizing Protaetia brevitarsis Larvae: Pathogenicity and Dose-Dependent Virulence - Haokun Cheng; Jialin Qiu; Muhammad Adeel Ghafar; Talim Hussain; Shimin Wang; Ritu Raj Poudyal; Liuyang Lu; Qin Feng; Liande Wang (Current Microbiology, 2026)

Spillover dynamics between maritime energy transportation and energy-related uncertainty - Adeel Riaz; Shek Ahmed; Tanzila Yeasmin Nilu; Muhammad Shahbaz (Regional Studies in Marine Science, 2026)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Green approaches for modifying lignocellulosic features: Recent advances in reducing recalcitrance for sustainable bioethanol production - Muhammad Adnan; Adeel Ahmed; Muhammad Rafiq; Nasim Ullah; Ali Ahmad; Muhammad Sarfraz; Raza Ullah; Muzamil Ahmad; Bing Yu; Hailin Cong (Biomass and Bioenergy, 2025)

Green Synthesis, Characterization, and Effect of Zinc Oxide Nanoparticles on Wheat (Triticum Aestivum L.) Under Cadmium Stress - Aqsa Khan; Samina Jam Nazeer Ahmad; Muhammad Jafir; Adeel Ahmad; Muhammad Irfan; Muhammad Qasim; Jam Nazeer Ahmad; Muhammad Azeem Sabir; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Enhancing mechanical and durability properties of bentonite-modified self-compacting concrete - Khawaja Adeel Tariq; Aashir Waleed; Jamil Ahmad; Fahad Ali; Naveed Ahmad; Muhammad Danish Nisar (Innovative Infrastructure Solutions, 2025)

A novel approach towards green extraction of environmentally friendly anthraquinone based natural dye from amaltas fruits for leather coloration - Shahid Adeel; Fatima Batool; Tanvir Ahmad; Marwa Bashir; Noman Habib; Muhammad Imran; Rony Mia (Sustainable Chemistry and Pharmacy, 2025)

Phosphorus counters arsenic phytotoxicity in wheat by activating riboflavin-mediated defense response rather than reducing arsenic accumulation - Erkai He; Muhammad Adeel; Jie Ji; Hao Qiu (Journal of Hazardous Materials, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Prevalence and integrated risk assessment of antibiotics from River Chenab Pakistan; human and ecotoxicological prospectives - Aqeel Mahmood; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Javed; Adeel Mahmood (Science of The Total Environment, 2025)

MnFe2O4 thin film electrodes via AACVD: A facile route for enhanced oxygen evolution reaction - Alishbah Zaka; Misha Aftab; Nudrat Fatima; Khola Mashood; Muhammad Adeel Asghar; Arshid Numan; Muhammad Sheraz Ahmad; Ali Haider; Mudassir Iqbal; Waqas Ali Shah; Muhammad Adil Mansoor (Fuel, 2025)

Plant-derived green metal nanoparticles as antibacterial, antifungal, and therapeutic agents: Advances, challenges, and perspectives - Rabia Zafar; Azeem Intisar; Muhammad Imran Din; Ahsan Sharif; Ejaz Ahmed; Adeel Afzal (Bioresource Technology Reports, 2025)

Hollow cavity engineering of MOF-derived hierarchical nitrogen-doped In2O3@carbon for efficient photocatalytic degradation of tetracycline hydrochloride - Raza Ullah; Muhammad Rafiq; Alamgir; Abdul Qadir; Adeel Ahmed; Muhammad Fayaz; Muhammad Adnan; Nasim Ullah; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Insights into the development of visible-light-induced CeO₂-TiO₂/g-C₃N₄ heterojunction catalysts for the mitigation of antibiotic pollutants - Amal Abdulrahman; Abdullah K. Alanazi; Hessa A. Alsalmah; Sidra Mubeen; Noureddine Elboughdiri; Atef E.L. Jery; Adeel Ahmed; Muhammad Aadil (Journal of Water Process Engineering, 2025)

Impact of Silicon-Based Treatments On the Demographic Traits of Spodoptera frugiperda in Maize - Muhammad Adeel Ghafar; Qin Feng; Inzamam Ul Haq; Moazam Hyder; Muhammad Sufian; Dilawar Abbas; Kamran Haider; Muhammad Lubaid Khalid; Muhammad Rahan Akhtar; Liande Wang; Rashid Iqbal; Noorah AlKubaisi; et al. (Journal of Crop Health, 2025)

Toxicity of Ethanolic Plant Extracts to Aphis gossypii, Bemisia tabaci, and Frankliniella occidentalis and Selectivity to Coccinella septempunctata and Menochilus sexmaculatus - Moazam Hyder; Faraz Ali; Muhammad Adeel Ghafar; Aslam Bukero; Inzamam ul Haq; Abdul Mubeen Lodhi; Youming Hou (Neotropical Entomology, 2025)

Seismic evaluation and strengthening of an RC building using different retrofit techniques in earthquake-prone region of Pakistan - Obaidullah Khan; Muhammad Faisal Javed; Adeel Zafar; Sanaullah Khan (Innovative Infrastructure Solutions, 2025)

Rapid and selective E-waste gold extraction from aqua regia by dual redox active-sites of skeleton modulated poly(organo)phosphazenes - Yasir Abbas; Sajjad Ali; Majid Basharat; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Mohamed Bououdina; Haoliang Wang; Niaz Ali Khan (Chemical Engineering Journal, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Multifunctional Magnetic Nanoparticles for Targeted Drug Delivery Against Cancer: A Review of Mechanisms, Applications, Consequences, Limitations, and Tailoring Strategies - Shumaila Riaz; Shaukat Ali; Muhammad Summer; Urva Akhtar; Shehzeen Noor; Rimsha Haqqi; Muhammad Adeel Farooq; Iqra Sardar (Annals of Biomedical Engineering, 2025)

Nano-selenium: a novel candidate for plant microbiome engineering - Muzammil Hussain; Muhammad Adeel; Jason C. White (Trends in Plant Science, 2025)

Non-leguminous green manures improve labile phosphorus availability and crop yield in agroecosystems: A global meta-analysis - Adnan Anwar Khan; Imran Azeem; Jing Hui; Yupei Chen; Yuqi Yuan; Tahir Shah; Muhammad Adeel; Noman Shakoor; Rana Muhammad Ammar Asghar; Weidong Cao; Dabin Zhang; Yajun Gao (Soil and Tillage Research, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Exploration of natural colourant of ( Solanum melongena L.) brinjal plant residues for fabric dyeing: a novel approach towards textile processing - Fatima Batool; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; Sahar Mumtaz; Muhammad Hussaan (Natural Product Research, 2025)

High-performance disposable electrochemical sensors for creatinine derived from hollow CoNi-LDH@Creatinine-imprinted Poly(methacrylic acid) (i-PMA) composites - Muhammad Faheem; Zohaib Saddique; Toheed Akhter; Kun Wang; Jing Qian; Wuyan Gu; Adeel Afzal; Lingliang Long (Analytica Chimica Acta, 2025)

Highly efficient degradation of norfloxacin by using Co3O4-CeO2 as a heterogeneous catalyst through peroxymonosulfate activation: Characterization, catalytic performance and mechanism - Muhammad Rafiq; Raza Ullah; Adeel Ahmed; Xin Liu; Muhammad Usman; Qinghua Cao; Muhammad Adnan; Muhammad Fayaz; Waqas Haider; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Impacts of soiling on solar panel performance and state-of-the-art effective cleaning methods: A recent review - Nadia Shahzad; Naveed Hussain; Shayan Umar; Muhammad Farooq Azam; Tanzeela Yousaf; Adeel Waqas (Journal of Cleaner Production, 2025)

The multifaceted roles of gut microbiota in insect physiology, metabolism, and environmental adaptation: implications for pest management strategies - Kamran Haider; Dilawar Abbas; Jose Galian; Muhammad Adeel Ghafar; Kamil Kabir; Muhammad Ijaz; Mehboob Hussain; Khalid Ali Khan; Hamed A. Ghramh; Abbas Raza (World Journal of Microbiology and Biotechnology, 2025)

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Seismic capacity assessment of eco-friendly fly ash brick masonry structures after retrofitting - Shah Zeb; Khan Shahzada; Umar Ahmad Noor; Muhammad Adeel Arshad; Abdur Rahim Khan; Haleem Ullah Khan (Innovative Infrastructure Solutions, 2025)

Chemically modified filter paper with Jaman fruit extract for visual sensing of milk freshness - Muhammad Naeem Shabbir; Adeel Ahmad; Muhammad Aslam; Ayaz Hassan; Hidayat Ullah; Muhammad Akram; Hafiza Fatima Qayum; Fatima Naeem (Food Chemistry, 2025)

Retraction Note: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity andAmeliorative Effects of Cinnamomum cassia in Sprague–Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2025)

The Role of Gut Microbiota in Shaping Immune Responses in Tephritidae Fruit Fly and Prospective Implications for Management - Kamran Haider; Muhammad Sufian; Dilawar Abbas; Kamil Kabir; Muhammad Shamekh Ali; Yasmin Kausar; Muhammad Adeel Ghafar (Neotropical Entomology, 2025)

Mitigation of zinc leaching from waste ground tire rubbers through polymer encapsulation - Muhammad Adeel; Yanou Fishel; Johan Blom; Freddy Dardenne; Bart Michielsen; Jef Bergmans; Lorenz Van Nueten; Cedric Vuye; Christophe M.L. Vande Velde; Pieter Billen (Waste Management, 2025)

Exploring heat transfer in freezing supercooled water droplet through high-speed infrared thermography - Hassan Abbas Khawaja; Samaneh Keshavarzi; Adeel Yousuf; Manaf Muhammed; Muhammad Shakeel Virk; Derek Harvey; Gelareh Momen (Cold Regions Science and Technology, 2025)

Comparative analysis to assess food security in south asian nations: an application of multivariate GARCH model - Shazia Kousar; Amina Ameer; Adeel Nasir; Muhammad Afzal; Sohail Abbas (Environment, Development and Sustainability, 2024)

Calcium oxide nanoparticles ameliorate cadmium toxicity in alfalfa seedlings by depriving its bioaccumulation, enhancing photosystem II functionality and antioxidant gene expression - Maqsood Ul Hussan; Sadam Hussain; Muhammad Adeel; Atif Ayub; Hafiz Abdul Kareem; Shaista Jabeen; Muhammad Saqib; Quanzhen Wang; Mingke Yan; Kadambot H.M. Siddique; Muhammad Tahir (Science of The Total Environment, 2024)

Spatial distribution and impacts of microplastics on potato growth and yield in agroecosystems in Sialkot, Pakistan - Zonaira Qaiser; Noreen Khalid; Adeel Mahmood; Zarrin Fatima Rizvi; Shiou Yih Lee; Muhammad Aqeel (Journal of Hazardous Materials, 2024)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

Two-dimensional Bi2Se3 nanosheets synthesis for efficient electrocatalytic production of ammonia from nitrate - Sadeeq Ullah; Aftab Ahmad; Majeed Ur Rehman; Ashfaq Ahmad; Shah Zada; Daxiang Cui; Hafiz Muhammad Adeel Sharif; Lu Li (Journal of Environmental Chemical Engineering, 2024)

Multilayered photo-bioanode for simultaneous conversion of CO2 and industrial refractory organics into bioelectricity in a microbial fuel cell system - Muhammad Ahmad; Maryam Yousaf; Aisha Batool; Hafiz Muhammad Adeel Sharif (Fuel, 2024)

Interactive use of biochar and chemical fertilizer for improving nutrient availability and crop growth in rainfed area - Saddam Hussain; Rifat Hayat; Saleem Ullah; Muhammad Ashraf; Rebwar Nasir Dara; Muhammad Adeel Ashraf; Sami Ullah Khan; Muyassar Norberdiyeva; Manish Gupta; M. Ijaz Khan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

De novo assembly of sialotranscriptome of Hyalomma anatolicum and insights into expression dynamics in response to Theileria annulata infection - Adeel Mumtaz Abbasi; Shiza Nasir; Amna Arshad Bajwa; Haroon Akbar; Sara Artigas-Jerónimo; Clara Muñoz-Hernández; Marta Sánchez-Sánchez; Alberto Moraga-Fernández; Isabel G. Fernández de Mera; José de la Fuente; Muhammad Imran Rashid (Experimental and Applied Acarology, 2024)

RETRACTED ARTICLE: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2024)

Enhanced activation of peroxymonosulfate by nanomagnetic CoFe2O4-CeO2/g-C3N4 composites as a heterogeneous catalyst for metronidazole degradation - Adeel Ahmed; Muhammad Usman; Muhammad Rafiq; Muhammad Adnan; Raza Ullah; Hailin Cong; Bing Yu (Journal of Water Process Engineering, 2024)

Unveiling the heterojunction of Fe3O4@MXene nanocatalyst for ultrafast degradation of antibiotics via non-radical pathway - Jintong Huang; Hafiz Muhammad Adeel Sharif; Ayyaz Mahmood; Changping Li (Chemical Engineering Journal, 2024)

Effects and fate of metal-based engineered nanomaterials in soil ecosystem: A review - Qibin WANG; Peng ZHANG; Weichen ZHAO; Shakoor NOMAN; Adeel MUHAMMAD; Guikai ZHU; Yi SUN; Quanlong WANG; Yaqi JIANG; Yukui RUI (Pedosphere, 2024)

Mn-MOF derived N-doped MnOx@carbon heterogeneous catalysts for Vis-light, S2O82, HSO5, Vis/S2O82, and Vis/HSO5-induced degradation of metronidazole: Kinetics and mechanistic study - Raza Ullah; Muhammad Rafiq; Alamgir; Adeel Ahmed; Xin Liu; Waqas Haider; Muhammad Fayaz; Qinghua Cao; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2024)

Impact of sea surface temperature in the Arabian Sea on the variability of Summer Monsoon Rainfall over Pakistan Region - Muhammad Adeel; Atteeq Razzak; Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Dynamics of Atmospheres and Oceans, 2024)

Green synthesis of graphene for targeted recovery of silver from photovoltaic waste - Muhammad Adeel Zafar; Yang Liu; Mohan V. Jacob (Chemosphere, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Modern ecofriendly approach for extraction of luteolin natural dye from weld for silk fabric and wool yarn dyeing - Syed Ali Raza Naqvi; Kaif ul-Wara; Shahid Adeel; Rony Mia; Mozhgan Hosseinnezhad; Luqman Jameel Rather; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Correction: Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Cryptic footprint of thallium in soil-plant systems; A review - Noman Shakoor; Samama Tariq; Muhammad Adeel; Imran Azeem; Muhammad Nadeem; Muhammad Zain; Yuanbo Li; Wang Quanlong; Rabia Aslam; Yukui Rui (Chemosphere, 2024)

Ce-TiO2 nanoparticles with surface-confined Ce3+/Ce4+ redox pairs for rapid sunlight-driven elimination of organic contaminants from water - Amna Jamil; Tehzeeb Sawaira; Asghar Ali; Muhammad Awais; Amir Habib; Tajamal Hussain; Ahsan Sharif; Naseer Iqbal; Adeel Afzal (Environmental Nanotechnology, Monitoring & Management, 2024)

Evaluating the Effect of pH, Temperature and Concentration on Antioxidant and Antibacterial Potential of Spectroscopically, Spectrophotometrically and Microscopically Characterized Mentha Spicata Capped Silver Nanoparticles - Tahreem Tanveer; Shaukat Ali; Nazish Mazhar Ali; Muhammad Adeel Farooq; Muhammad Summer; Ali Hassan; Fareha Ali; Muhammad Irfan; Lubna Kanwal; Hafsa Shahzad; Rahila Islam (Journal of Fluorescence, 2024)

A fuzzy classification method based on rules learning for shaded and unshaded hotspot faults on photovoltaic modules - Junaid Ali Khan; Shengxue Tang; Borui Ji; Fahad Khan; Muhammad Adeel Khan; Usman Khan Khalil; Irshad Ullah (Journal of Cleaner Production, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Unlocking Triticum aestivum L. resilience: Exogenous proline's remarkable role in mitigating lead stress, and delving into the secrets of TaGSK1 gene expression - Sidra Balooch; Sibgha Noreen; Seema Mahmood; Nida Zahra; Ahmad Azeem; Muhammad Mohsin Altaf; Muhammad Salim Akhter; Adeel Abbas (South African Journal of Botany, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

Enhancing silk dyeing with eco-friendly colorant extracted from Cassia fistula brown pods using green mordants - Mariam Younis; Shahid Adeel; Muhammad Zulqurnain Haider; Rony Mia; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Ecofriendly process optimization of natural dye extraction from clove (Syzygium aromaticum L.) using response surface methodology and artificial neural network modeling - Muhammad Aftab; Tanvir Ahmad; Shahid Adeel; Maria Javed (Sustainable Chemistry and Pharmacy, 2024)

Microwave-assisted cleaner extraction of tannin from Terminalia chebula: A promising green method for sustainable leather dyeing - Marwa Bashir; Shahid Adeel; Muhammad Aftab; Rony Mia; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Risk surveillance with spatial distribution of Organochlorine Pesticides (OCPs) from sedimentary samples of Chenab River - Sidra Siddique; M. Nawaz Chaudhry; Sajid Rashid Ahmad; Rabia Nazir; Rimsha Javed; Muhammad Rashid Hafeez; Yasser Alraey; Lalita Ambigai Sivasamugham; Adeel Mahmood (Science of The Total Environment, 2024)

Progress in layered double hydroxides (LDHs): Synthesis and application in adsorption, catalysis and photoreduction - Ahmad Farhan; Aman Khalid; Nimra Maqsood; Sidra Iftekhar; Hafiz Muhammad Adeel Sharif; Fei Qi; Mika Sillanpää; Muhammad Bilal Asif (Science of The Total Environment, 2024)

A review of infrared thermography applications for ice detection and mitigation - Adeel Yousuf; Hassan Khawaja; Muhammad S. Virk (Cold Regions Science and Technology, 2024)

Redox mediators boost NOx reduction via trade-off electron charges using a cube-shaped (cMn@rGO) catalyst; mechanism and electrochemical study - Hafiz Muhammad Adeel Sharif; Jintong Huang; Kifayatullah Khan; Shahzad Afzal; Changping Li (Chemosphere, 2024)

Lithium-induced alterations in soybean nodulation and nitrogen fixation through multifunctional mechanisms - Noman Shakoor; Muzammil Hussain; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Peng Zhang; Yuanbo Li; Wang Quanlong; Robert Horton; Yukui Rui (Science of The Total Environment, 2023)

Efficient heterogeneous activation of peroxymonosulfate by manganese-doped LaCoO3 perovskites for metronidazole degradation: A mechanistic study and reaction pathways - Muhammad Rafiq; Adeel Ahmed; Muhammad Usman; Raza Ullah; Fengyuan Gao; Muhammad Mateen; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

State-of-the-art analysis of the fuel desulphurization processes: Perspective of CO2 utilization in coal biodesulphurization - Muhammad Ahmad; Maryam Yousaf; Jing-Cheng Han; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Linlin Wang; Zhaozhao Tang; Yang Zhou; Yuefei Huang (Chemical Engineering Journal, 2023)

Variation in Soil C and P Fractions Associated with Microbial Biomass - Khuram Shehzad Khan; Muhammad Naveed; Muhammad Farhan Qadir; Adeel Ahmad; Hafiz Hassan Javed; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2023)

Conceptual design of cost-effective ice detection system based on infrared thermography - Adeel Yousuf; Hassan Khawaja; Muhammad S. Virk (Cold Regions Science and Technology, 2023)

Environmental friendly utilization of plant wastes in combination as a source of natural colorants for binary mordanted silk dyeing - Nimra Amin; Shahid Adeel; Fazal-ur-Rehman; Muhammad Naveed Anjum (Environmental Science and Pollution Research, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Opportunities and challenges in mitigating nutrient stress in plants via melatonin-mediated signaling pathways - Aitezaz A.A. Shahani; Adeel Abbas; Junaid Ali Siddiqui; Sana Ullah; Rashida Hameed; Tianzhuo Cheng; Muhammad Ahsan Asghar; Amna Fayyaz; Khalid Ali Khan; Taimoor Hassan Farooq (South African Journal of Botany, 2023)

Microwave-assisted santalin extraction from Pterocarpus santalinus for mordanted woolen yarn dyeing - Maria Mahboob; Shahid Adeel; Samra Barkaat; Tanvir Ahmad; Meral Özomay; Rony Mia; Somayeh Mirnezhad; Muhammad Zuber (Sustainable Chemistry and Pharmacy, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Recent developments in designing Cu-based electrocatalysts and advanced strategies for electrochemical nitrate reduction to ammonia - Sadeeq Ullah; Shiyong Wang; Changping Li; Amin Ullah Jan; Fei Zhan; Hafiz Muhammad Adeel Sharif; Qingling Liu; Gang Wang (Journal of Environmental Chemical Engineering, 2023)

Reduced graphene oxide supported CoFe2O4 composites with enhanced peroxymonosulfate activation for the removal of sulfamethoxazole: Collaboration of radical and non-radical pathways - Adeel Ahmed; Muhammad Usman; Zhijian Ji; Muhammad Rafiq; Raza Ullah; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Distribution, bioaccumulation, and health risk assessment of organochlorines across the riverine ecosystem of Punjab Province, Pakistan - Mujtaba Baqar; Samra Naseem; Amtul Bari Tabinda; Yiming Yao; Muhammad Shahzad; Adeel Mahmood; Abdullah Yasar; Shizhen Zhao; Gan Zhang; Hongwen Sun (Environmental Science and Pollution Research, 2023)

Strategic analysis on development of simultaneous adsorption and catalytic biodegradation over advanced bio-carriers for zero-liquid discharge of industrial wastewater - Jing-Cheng Han; Muhammad Ahmad; Maryam Yousaf; Shafeeq Ur Rahman; Hafiz Muhammad Adeel Sharif; Yang Zhou; Bo Yang; Yuefei Huang (Chemosphere, 2023)

Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - Yousra Riaz; Samra Barkaat; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Muhammad Zuber; Meral Ozomay; Shahnaz Parveen Khattak (Environmental Science and Pollution Research, 2023)

Editorial: Occurrence, migration and degradation of emerging organic pollutants in the estuarine environment - Qing Luo; Muhammad Adeel; Muhammad Arslan Ahmad; Guangzhe Jin; Muhammad Zain (Frontiers in Marine Science, 2023)

Visible light-driven photocatalytic bacterial inactivation on PPE, supported by the DFT and bactericidal study - Gulzar Ahmed; Adeel Rasheed; Khurram Shahzad Munawar; Satesh Bandaru; Javid Khan; Zhongwu Liu; Muhammad Sheraz Ahmad (Environmental Science and Pollution Research, 2023)

Construction and elucidation of zerovalent iron@terephthalic acid/iron oxide catalyst to activate peroxymonosulfate for accelerating and long-lasting NOx removal - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Kifayatullah Khan; Yang Cai; Xu Xiao; Changping Li (Chemical Engineering Journal, 2023)

Does financial development influence the overall natural environment? An environmental performance index (EPI) based insight from the ASEAN countries - Rana Muhammad Adeel-Farooq; Jimoh Olajide Raji; Ghulam Muhmmad Qamri (Environment, Development and Sustainability, 2023)

Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - Shahid Adeel; Hira Akram; Muhammad Usman; Tanveer Hussain Bokhari; Muhammad Aftab; Meral Ozomay (Environmental Science and Pollution Research, 2023)

Integrative Evaluation of the Ecological Hazards by Microplastics and Heavy Metals in Wetland Ecosystem - Shanza Zaka; Muhammad Aqeel; Adeel Mahmood; Ali Noman; Zarrin Fatima Rizvi; Wajiha Sarfraz; Aisha Nazir; Komal Arshad; Noreen Khalid (Bulletin of Environmental Contamination and Toxicology, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Nitrite sensor using activated biochar synthesised by microwave-assisted pyrolysis - Scarlett Allende; Yang Liu; Muhammad Adeel Zafar; Mohan V. Jacob (Waste Disposal & Sustainable Energy, 2023)
Developing applications for the by-products obtained from waste processing is vital for resource recovery. The synthesis of ZnCl 2 -activated biochar with high electrocatalytic activity was carried out by the microwave-assisted pyrolysis of pineapple peel and subsequent chemical activation process. Activated biochar is employed in the electrochemical sensing of nitrite by drop casting in a glassy carbon electrode (GCE). The activated biochar exhibited a stacked carbon sheet, 254 m 2 g −1 Brunauer, Emmett and Teller (BET) surface area, 0.076 cm 3 g −1 pore volume, 189.53 m 2 g −1 micropore area and oxygen-containing functional groups. The electrochemical impedance spectroscopy of the modified GCE showed a reduced charge transfer resistance of 61%. This is crucial to determine the electrochemical properties of biochar. The sensor showed a significant current response and an excellent limit of detection of 0.97 µmol L −1 . The modified-activated biochar electrochemical sensor demonstrated high selectivity, reproducibility (RSD=2.4%), and stability (RSD=2.6%). Graphical abstract

Antagonistic impact on cadmium stress in alfalfa supplemented with nano-zinc oxide and biochar via upregulating metal detoxification - Hafiz Abdul Kareem; Muhammad Adeel; Muhammad Azeem; Muhammad Arslan Ahmad; Noman Shakoor; Mahmood Ul Hassan; Sana Saleem; Annie Irshad; Junpeng Niu; Zhipeng Guo; Ćupina Branko; Roman Hołubowicz; et al. (Journal of Hazardous Materials, 2023)

Forage potential of several halophytic species grown on saline soil in arid environments - Hadi Pirasteh-Anosheh; Gholamhassan Ranjbar; Nudrat Aisha Akram; Muhammad Adeel Ghafar; Antonio Panico (Environmental Research, 2023)

UAV-based multi-sensor data fusion and machine learning algorithm for yield prediction in wheat - Shuaipeng Fei; Muhammad Adeel Hassan; Yonggui Xiao; Xin Su; Zhen Chen; Qian Cheng; Fuyi Duan; Riqiang Chen; Yuntao Ma (Precision Agriculture, 2023)

Microwave-assisted sustainable exploration of cocklebur leaves (Xanthium strumarium L.) as a novel source of distinct yellow natural colorant for dyeing cotton fabric - Muhammad Hussaan; Ahmad Raza; Noman Habib; Shahid Adeel; Naeem Iqbal; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2023)

Ecological health risk assessment of microplastics and heavy metals in sediments, water, hydrophytes (Alternanthera philoxeroides, Typha latifolia, and Ipomoea carnea), and fish (Labeo rohita) in Marala wetlands in Sialkot, Pakistan - Komal Arshad; Muhammad Aqeel; Ali Noman; Atia Nazir; Adeel Mahmood; Zarrin Fatima Rizvi; Wajiha Sarfraz; Sajjad Hyder; Shanza Zaka; Noreen Khalid (Environmental Science and Pollution Research, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Spontaneous intra-electron transfer within rGO@Fe2O3-MnO catalyst promotes long-term NOx reduction at ambient conditions - Hafiz Muhammad Adeel Sharif; Muhammad Bilal Asif; Yuwei Wang; Ya-Nan Hou; Bo Yang; Xu Xiao; Changping Li (Journal of Hazardous Materials, 2023)

Environment relevant concentrations of lithium influence soybean development via metabolic reprogramming - Noman Shakoor; Muhammad Adeel; Muhammad Arslan Ahmad; Muzammil Hussain; Imran Azeem; Muhammad Zain; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Journal of Hazardous Materials, 2023)

Performance analysis of a stand-alone thermal energy storage system based on CSM plates filled with phase change material - Hafiz Muhammad Adeel Hassan; Mads Peter Rudolph Hansen; Jonathan Dallaire; Martin Anker Boesen Larsen; Esther Kieseritzky; Joe Alexandersen; Christian Veje; Ivar Lund (Energy and Buildings, 2023)

Chemopreventive role of probiotics against cancer: a comprehensive mechanistic review - Shehzeen Noor; Shaukat Ali; Shumaila Riaz; Iqra Sardar; Muhammad Adeel Farooq; Ayesha Sajjad (Molecular Biology Reports, 2023)

Efficient photocatalytic degradation of Rhodamine B dye using solar light-driven La˗Mn co-doped Fe2O3 nanoparticles - Sobia Maqbool; Adeel Ahmed; Arif Mukhtar; Muhammad Jamshaid; Aziz Ur Rehman; Saima Anjum (Environmental Science and Pollution Research, 2023)

Assessment of wild turmeric–based eco-friendly yellow natural bio-colorant for dyeing of wool fabric - Noman Habib; Aamir Ali; Shahid Adeel; Fazal-ur-Rehman; Muhammad Aftab; Asma Inayat (Environmental Science and Pollution Research, 2023)

Efficacy of Different Endophytic Bacterial Strains in Enhancing Growth, Yield, and Physiological and Biochemical Attributes of Linum usitatissimum L - Khuram Shehzad Khan; Muhammad Farhan Qadir; Adeel Ahmad; Muhammad Naveed; Taqi Raza; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2022)

Agricultural Applications and Potential Risks of Copper-Based Nanoagrochemicals in Crop Cultivation - Yanwanjing Liu; Weichen Zhao; Yongguang Yin; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Zhiqiang Tan; Yukui Rui; Qinghua Zhang; Jingfu Liu; Baoshan Xing (Reviews of Environmental Contamination and Toxicology, 2022)

Sustainable eco-friendly extraction of yellow natural dye from haar singhar (Nyctanthes arbor-tritis) for bio coloration of cotton fabric - Muhammad Yameen; Shahid Adeel; Hunaira Nasreen; Fazal-ur-Rehman; Abdul Ghaffar; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Environmental friendly silk and cotton dyeing using natural colorant of Bougainvillea (Bougainvillea glabra) flowers: the sustainable approach towards textile industry - Warda Rasool; Shahid Adeel; Fatima Batool; Sheikh Asrar Ahmad; Sahar Mumtaz; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Effects of two Mn-based nanomaterials on soybean antioxidant system and mineral element homeostasis - Yaqi Jiang; Pingfan Zhou; Tengtao Ma; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Mingshu Li; Manlin Guo; Yukui Rui (Environmental Science and Pollution Research, 2022)

An active learning method for diabetic retinopathy classification with uncertainty quantification - Muhammad Ahtazaz Ahsan; Adnan Qayyum; Adeel Razi; Junaid Qadir (Medical & Biological Engineering & Computing, 2022)

Environmental friendly pollution free bio-dyeing of wool with haar singhar (Coral Jasmine) flower extract - Shahid Adeel; Sehrish Ahmad; Noman Habib; Muhammad Jawwad Saif; Fatima Batool; Muhammad Aftab (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Heavy metal pollution in the soil of a riverine basin: distribution, source, and potential hazards - Kifayatullah Khan; Abdul Mohsin; Hafiz Muhammad Adeel Sharif; Afsheen Maryam; Jafar Ali; Xu Li; Sobhy Mostafa Ibrahim; Muhammad Ayaz; Yunqiao Zhou; Muhammad Younas (Environmental Monitoring and Assessment, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Comparative Effect of Various Organic Extracts Coated Urea Fertilizer on the Release Pattern of Ammonium and Nitrate in the Soil at Different Time Intervals - Adeel Ahmad; Muhammad Yaseen; Hafiz Naeem Asghar; Shahzad Maqsood Ahmed Basra (Journal of Soil Science and Plant Nutrition, 2022)

Sustainable natural coloring potential of bitter gourd (Momordica charantia L.) residues for cotton dyeing: innovative approach towards textile industry - Fatima Batool; Shahid Adeel; Naeem Iqbal; Muhammad Azeem; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Sustainable isolation of licorice (Glycyrrhiza glabra L.)-based yellow natural colorant for dyeing of bio-mordanted cotton - Shahid Adeel; Shumaila Kiran; Mazhar Abbas; Fatima Batool; Muhammad Hussaan; Nimra Amin (Environmental Science and Pollution Research, 2022)

Evaluation of ceiling fan dust as an indicator of indoor PCBs pollution in selected cities of Punjab, Pakistan: implication on human health - Foqia Khalid; Abdul Qadir; Muhammad Zaffar Hashmi; Adeel Mehmood; Iqra Aslam; Gan Zhang; Zulkifl Ahmed (Arabian Journal of Geosciences, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Removing Hexavalent Chromium by Nano Zero-Valent Iron Loaded on Attapulgite - Yuzhen Wei; Muhammad Usman; Muhammad Farooq; Muhammad Adeel; Fasih Ullah Haider; Zhandong Pan; Weiwei Chen; Hongyan Liu; Liqun Cai (Water, Air, & Soil Pollution, 2022)

New approach in SARS-CoV-2 surveillance using biosensor technology: a review - Dina M. El-Sherif; Mohamed Abouzid; Mohamed S. Gaballah; Alhassan Ali Ahmed; Muhammad Adeel; Sheta M. Sheta (Environmental Science and Pollution Research, 2022)

Ecofriendly application of coconut coir (Cocos nucifera) extract for silk dyeing - Shahid Adeel; Shumaila Kiran; Muhammad Shahid; Sajid Raza Habib; Noman Habib; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan - Muhammad Ashraf; Adnan Arshad; Praharsh M. Patel; Adeel Khan; Huma Qamar; Ristina Siti-Sundari; Muhammad Usman Ghani; Ali Amin; Jamilur Rehman Babar (Natural Hazards, 2021)

Aging and its treatment with vitamin C: a comprehensive mechanistic review - Shumaila Mumtaz; Shaukat Ali; Hafiz Muhammad Tahir; Syed Akif Raza Kazmi; Hafiz Abdullah Shakir; Tafail Akbar Mughal; Samaira Mumtaz; Muhammad Summer; Muhammad Adeel Farooq (Molecular Biology Reports, 2021)

Exploring factors of the sustainable supply chain in the post-COVID-19 pandemic: SWARA approach - Khizar Hayat; Zhu JianJun; Sharafat Ali; Muhammad Adeel Khan (Environmental Science and Pollution Research, 2021)

Exploring natural colorant behavior of husk of durum (Triticum durum Desf.) and bread (Triticum aestivum L.) wheat species for sustainable cotton fabric dyeing - Ali Ahmad Khan; Shahid Adeel; Muhammad Azeem; Naeem Iqbal (Environmental Science and Pollution Research, 2021)

Environmental friendly extraction of walnut bark-based juglone natural colorant for dyeing studies of wool fabric - Waseem-ul- Arifeen; Fazal-Ur- Rehman; Shahid Adeel; Muhammad Zuber; Mirza Nadeem Ahmad; Tanvir Ahmad (Environmental Science and Pollution Research, 2021)

Revisiting the Effects of Different Dietary Sources of Selenium on the Health and Performance of Dairy Animals: a Review - Muhammad Adeel Arshad; Hossam Mahrous Ebeid; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Role of sea-level pressure of Arabian Sea on variability of summer monsoon rainfall over Northern Pakistan - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal; Muhammad Adeel (Theoretical and Applied Climatology, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Graphitic carbon nitride (g-C3N4) alleviates cadmium-induced phytotoxicity to rice (Oryza sativa L.) - Yi Hao; Ruitao Lv; Chuanxin Ma; Muhammad Adeel; Ziqian Zhao; Yuhang Rao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Biosynthesis and industrial applications of α-amylase: a review - Muhammad Adeel Farooq; Shaukat Ali; Ali Hassan; Hafiz Muhammad Tahir; Samaira Mumtaz; Shumaila Mumtaz (Archives of Microbiology, 2021)

CO2 from waste to resource by developing novel mixed matrix membranes - Adeel Shakoor; Asim Laeeq Khan; Parveen Akhter; Muhammad Aslam; Muhammad Roil Bilad; Ibrahim M. Maafa; Konstantinos Moustakas; Abdul-Sattar Nizami; Murid Hussain (Environmental Science and Pollution Research, 2021)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Bisphenol-A induced antioxidants imbalance and cytokines alteration leading to immune suppression during larval development of Labeo rohita - Mehwish Faheem; Muhammad Adeel; Saba Khaliq; Khalid P. Lone; Alaa El-Din-H-Sayed (Environmental Science and Pollution Research, 2020)

Appraisal of wheat genomics for gene discovery and breeding applications: a special emphasis on advances in Asia - Awais Rasheed; Shigeo Takumi; Muhammad Adeel Hassan; Muhammad Imtiaz; Mohsin Ali; Alex I. Morgunov; Tariq Mahmood; Zhonghu He (Theoretical and Applied Genetics, 2020)

Harnessing natural colorants from algal species for fabric dyeing: a sustainable eco-friendly approach for textile processing - Muhammad Azeem; Naeem Iqbal; Riffat Ayesha Mir; Shahid Adeel; Fatima Batool; Ali Ahmad Khan; Sadaf Gul (Journal of Applied Phycology, 2019)

Green algae, Cladophora glomerata L.–based natural colorants: dyeing optimization and mordanting for textile processing - Riffat Ayesha Mir; Shahid Adeel; Muhammad Azeem; Fatima Batool; Ali Ahmad Khan; Sadaf Gul; Naeem Iqbal (Journal of Applied Phycology, 2019)

Ultrasonic assisted improved extraction and dyeing of mordanted silk fabric using neem bark as source of natural colourant - Shahid Adeel; Khalid Mahmood Zia; Muhammad Abdullah; Fazal-ur- Rehman; Mahwish Salman; Mohammad Zuber (Natural Product Research, 2019)

Correction to: Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Ecological risk assessment of metals in sediments and selective plants of Uchalli Wetland Complex (UWC)—a Ramsar site - Sumera Gull Bhatti; Amtul Bari Tabinda; Faisal Yasin; Adeel Mehmood; Muhammad Salman; Abdullah Yasar; Rizwan Rasheed; Rabia Wajahat (Environmental Science and Pollution Research, 2019)

Assessment of organochlorine pesticides in the Himalayan riverine ecosystems from Pakistan using passive sampling techniques - Rizwan Ullah; Rehana Asghar; Mujtaba Baqar; Adeel Mahmood; Syeda Nazish Ali; Muhammad Sohail; Ralf B. Schäfer; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2019)

Assessment of genetic diversity in round gourd (Praecitrullus fistulosus) germplasm of Pakistan considering morphological characters - Adeel Shahid; Chaudhary Muhammad Ayyub; Mazhar Abbas; Rashid Ahmad (Genetic Resources and Crop Evolution, 2019)

Natural and synthetic estrogens in leafy vegetable and their risk associated to human health - Muhammad Adeel; Muhammad Zain; Shah Fahad; Muhammad Rizwan; Asif Ameen; Hao Yi; Mansoor A. Baluch; Jie Yinn Lee; Yukui Rui (Environmental Science and Pollution Research, 2018)

Levels, distribution, and sources of organophosphate flame retardants and plasticizers in urban soils of Shenyang, China - Qing Luo; Yue Shan; Adeel Muhammad; Shiyu Wang; Lina Sun; Hui Wang (Environmental Science and Pollution Research, 2018)

A novel homozygous mutation in SZT2 gene in Saudi family with developmental delay, macrocephaly and epilepsy - Muhammad Imran Naseer; Mohammad Khalid Alwasiyah; Angham Abdulrahman Abdulkareem; Rayan Abdullah Bajammal; Carlos Trujillo; Muhammad Abu-Elmagd; Mohammad Alam Jafri; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2018)

Monitoring and spatiotemporal variations of pyrethroid insecticides in surface water, sediment, and fish of the river Chenab Pakistan - Ghazala Riaz; Amtul Bari Tabinda; Muhammad Kashif; Abdullah Yasar; Adeel Mahmood; Rizwan Rasheed; Muhammad Imran Khan; Javed Iqbal; Sidra Siddique; Yusra Mahfooz (Environmental Science and Pollution Research, 2018)

Microwave-assisted extraction and dyeing of chemical and bio-mordanted cotton fabric using harmal seeds as a source of natural dye - Shahid Adeel; Muhammad Zuber; Fazal-ur-Rehman; Khalid Mahmood Zia (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity and Ameliorative Effects of Cinnamomum cassia in Sprague-Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

Antiplatelet activity, molecular docking and QSAR study of novel N′-arylmethylidene-3-methyl-1-phenyl-6-p-chlorophenyl-1H-pyrazolo[3,4-b] pyridine-4-carbohydrazides - Ayesha Ramzan; Sara Siddiqui; Ahmad Irfan; Abdullah G. Al-Sehemi; Aftab Ahmad; Francis Verpoort; Adeel H. Chughtai; Misbahul A. Khan; Munawar A. Munawar; Muhammad Asim Raza Basra (Medicinal Chemistry Research, 2018)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

A novel homozygous frameshift variant in the MCPH1 gene causes primary microcephaly in a consanguineous Saudi family - Muhammad Imran Naseer; Mahmood Rasool; Osama Yousef Muthaffar; Abdulrahman J. Sabbagh; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2017)

Modulation of Wnt signaling pathway by hepatitis B virus - Muhammad Daud; Muhammad Adeel Rana; Tayyab Husnain; Bushra Ijaz (Archives of Virology, 2017)

Nickel stressed responses of rice in Ni subcellular distribution, antioxidant production, and osmolyte accumulation - Muhammad Rizwan; Muhammad Imtiaz; Zhihua Dai; Sajid Mehmood; Muhammad Adeel; Jinchang Liu; Shuxin Tu (Environmental Science and Pollution Research, 2017)

Microwave-assisted enhancement of milkweed (Calotropis procera L.) leaves as an eco-friendly source of natural colorants for textile - Muhammad Hussaan; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; M. Tariq Javed; Ali Raza (Environmental Science and Pollution Research, 2017)

Exploring factors influencing farmers’ willingness to pay (WTP) for a planned adaptation programme to address climatic issues in agricultural sectors - Adeel Ahmed; Muhammad Mehedi Masud; Abul Quasem Al-Amin; Siti Rohani Binti Yahaya; Mahfuzur Rahman; Rulia Akhtar (Environmental Science and Pollution Research, 2015)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

A missense mutation (p.G274R) in gene ASPA causes Canavan disease in a Pakistani family - Rashida Hussain; Shakeela Daud; Naseebullah Kakar; Adeel Ahmad; Abdul Hameed Baloch; Abdul Malik Tareen; Muhammad Azam Kakar; Jamil Ahmad (Molecular Biology Reports, 2012)